Anti-multidrug resistance Staphylococcus aureus (MRSA) potential of Macaranga gigantea - Mat Amin, ‪Nor Datiakma; Alias, Noraliza; Syed Osman Idid, Syed Zahir Idid; Mansor, Marzalina; Mohd. Salleh, Hamzah; Jalali, Saeid Reza Doust; Mohtar, Mastura (2010)
Multidrug resistance Staphylococcus aureus (MRSA) is a major threat to health sector worldwide due to their prevalence, intrinsic virulence & limited therapeutic means. MRSA infections complicate therapy and could double the mortality rate amongst the immuno-compromised, the elderly, infants and patients at the surgical and burnt units. The cost to treat hospitalized patients with MRSA infections is estimated to be between $3.2 billion to $4.2 billion per-annum. The emergence of community-acquired MRSA (CA-MRSA) and vancomycin-resistant (VRE) globally indicates that our current treatment for MRSA infection is getting more complicated and needs replenishment. Therefore, the search for an alternative anti-MRSA agent is very important to cater to this issue. Our research discovered the potential plant derived anti-MRSA agent derived from crude extract from leaves of Macaranga gigantea. M. gigantea is rich in alkaloids and tannins and traditionally used among the aboriginal tribes in Borneo to treat fungal infection and stomach aches. In this study, ethanol extract of M. gigantea was found active in inhibiting and killing MRSA at 0.313 mg/ml (MIC and MBC) with extraction recovery yield is approximately 11.1% (W/W). Instead of anti-MRSA potential, the extract of M. gigantea also found active against bacteria Eschericia col (MIC and MBC: 0.156 mg/ml) and fungus strain tryptophyton rubrum (MIC and MBC: 0.613 mg/ml). Acute oral toxicity studies adapting the OECD Guideline was conducted for 7 consecutive days on mice. The study conducted demonstrates that the median Lethal Dose (LD50) of the extract is more than 5g/kg of bodyweight and considered very low toxicity as compared with Vancomycin (LD50: 5g/kg of bodyweight) and table salt (LD50: 4g/kg of bodyweight). This extract is applicable in the sanitary industry, for example it can be useful in medical vicinities, hotels, for home usage, as well as food hygiene aspects where is a high risk of contamination by MRSA.